The abandonment issue of the imprescriptible pretensions - Alfaro, Luis (2017)
In this article, the issue around abandonment in judicial proceedings (Procedural abandonment) related with the imprescriptible pretensions will be analyzed, with a special mention to those relative to the right to property. The issue discussed in the National Jurisdictional Plenary of Civil Law and Civil Procedure of 2016 will be criticized. The true issue to be solved is revealed, it’s the one related to the imprescriptible pretensions as case of inappropriateness of abandonment. It raises reasons that put in question the normative provision that links the procedural abandonment with those pretensions. Precisely because of the lack of strong arguments to justify the relation, a necessary legislative amendment is proposed.